2014
DOI: 10.1590/0100-2945-215/13
|View full text |Cite
|
Sign up to set email alerts
|

Fisiologia do amadurecimento de mamões de variedades comercializadas no Brasil

Abstract: RESUMO -A emissão de etileno, a respiração e as transformações físicas e químicas em mamões da cv Golden e dos híbridos Tainung 01 e UENF/CALIMAN01 (UC01), colhidos no estádio 0 de maturação (fruto maturo com casca 100% verde) e mantidos a 25ºC° e 80% % UR foram avaliados durante a fase de amadurecimento. Os resultados mostram diferenças significativas entre os genótipos, em todas as características avaliadas. O mamão 'Golden' apresentou taxas respiratória e de emissão de etileno bastante superiores às registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
4
3
2
3
Order By: Relevance
“…Results above that observed by Silva (2016), which found an average of approximately 0.1% in fruits of papaya "Tainung 1". Souza et al (2014a) obtained an average of 0.09% of citric acid for papayas of the same variety, as well as found by Freitas et al (2018). Silva (2019) obtained mean values equal to 82 mg/100 g of vitamin C for fruits at the beginning of storage time, being found in this study an average of 38.01 mg/100 g. Nunes et al (2017) found mean values above 60 mg/100 g of vitamin C in Formosa papayas coated with cassava starch.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Results above that observed by Silva (2016), which found an average of approximately 0.1% in fruits of papaya "Tainung 1". Souza et al (2014a) obtained an average of 0.09% of citric acid for papayas of the same variety, as well as found by Freitas et al (2018). Silva (2019) obtained mean values equal to 82 mg/100 g of vitamin C for fruits at the beginning of storage time, being found in this study an average of 38.01 mg/100 g. Nunes et al (2017) found mean values above 60 mg/100 g of vitamin C in Formosa papayas coated with cassava starch.…”
Section: Resultssupporting
confidence: 87%
“…There were no significant differences between treatments for fruit firmness. The mean found for this variable was 6.69 N, a value lower than the mean found by Souza et al (2014a), which was about 20 N, and even lower than the value obtained by Barros et al (2018), which was about 48 N for papaya marketed in Campina Grande, PB, Brazil. Figure 3 shows the results of the external color analysis of the fruits submitted to the coatings.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations